Cerebral venous sinus thrombosis a study to assess clinical profile among female patients in a tertiary care hospital - Gujjar, Amruth; Babu, Sudindra; E., Kalinga B. (International Journal of Advances in Medicine, 2019)
Background: The Incidence of Cerebral Venous Thrombosis (CVT) is around 3-4 cases among one million population affecting children and young adults. In India the puerperal CVT is 10-12 times more common than western countries. Even though there is apparent “rarity” of the condition but advances in knowledge and available investigation in terms of imaging (CT scan/MRI) diagnosis can be done early for appropriate treatment and decreasing the morbidity and mortality. Methods: A prospective study was conducted at Karnataka Institute of Medical Sciences, Hubli, Karnataka from December 2014 to November 2015. A total of 36 patients were included in the study. Results: Mean age of females in the study was 27.06±9.033years. 75% had seizures, 47.2% had headache, 19.4% had focal neurological deficit, 13.9% had altered sensorium, 8.3% had cranial nerve deficits 5.6% had speech deficits. 72.22% of patients and were in peripartum period and 27.8% were non-pregnant. 72.2% had superior sagittal sinus involvement, 47.2% had transverse sinus, 47.2% had sigmoid sinus, and 13.9% had internal jugular vein and 5.6% straight sinus. 47.2% had single sinus involvement, and 52.8% had multiple sinus involvement. 94.4% patients were managed conservatively and 5.6% were managed by neurosurgical intervention. 94.4% patients survived and 5.6% had mortality. Conclusions: Cerebral venous sinus thrombosis is most common in young females during peripartum period. Early diagnosis, treatment and if necessary neurosurgical intervention has good outcome.